The Role of the Al-Ikhlas Mosque Da’i in Enhancing Religious and Social Awareness in the Peripheral Community - Ikhwan Soleh Harahap; Muniruddin Muniruddin (Madania: Jurnal Ilmu-Ilmu Keislaman, 2026)
Islam presents a moral framework in which spirituality and social responsibility are closely interconnected, encouraging individuals to embody religious values in everyday social life. However, in many peripheral communities, the presence of religious activities does not always lead to sustained ethical transformation or stronger social cohesion. This study aims to examine how da’i (Islamic preachers) in Gunung Tua, North Padang Lawas Regency, construct and implement dakwah strategies to enhance religious awareness and social engagement within a complex peripheral urban context. This research employs a qualitative case study approach to explore dakwah as a socially embedded practice shaped by relational, cultural, and structural dynamics. Data were collected through semi-structured interviews, participant observation, and documentation involving twelve informants, including da’i, mosque administrators, congregants, and community leaders. The data were analyzed using open, axial, and selective coding. The findings reveal that the role of da’i extends beyond ritual preaching to function as relational moral mediators within the community. Religious awareness develops through sustained interaction, informal counseling, and active community involvement. While dakwah bil-lisan remains the dominant method, its effectiveness is enhanced through dialogical communication, the use of local language, and relatable narratives. Additionally, dakwah bil-haal, reflected in exemplary behavior and social participation, strengthens the credibility of religious messages. The effectiveness of dakwah is influenced by supporting factors such as community trust and institutional support, as well as challenges including economic constraints and digital influences.